Method for improving density of copper alloy part

By combining the adhesive jet 3D printing process with vacuum heat curing, degreasing and segmented sintering processes, the problems of insufficient melting and low sintering density during 3D printing are solved, and the high density and excellent mechanical properties of copper alloy parts are achieved.

CN119525515APending Publication Date: 2025-02-28SHARED INTELLIGENT EQUIPMENT (ANHUI) CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411722152.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the 3D printing process, copper alloys are inadequately melted and heat diffused rapidly due to high reflectivity and high thermal conductivity, which affects the molding quality. The adhesive jet technology has low sintering density, which affects the mechanical properties and thermal conductivity of the components.

Method used

The dried copper alloy powder is coated layer by layer through the adhesive spraying 3D printing process and selectively sprayed the adhesive. After vacuum heat curing, vacuum degreasing and segmented sintering, the parts are ensured to have high density and excellent mechanical properties.

Benefits of technology

Through this method, the density and mechanical properties of copper alloy parts are significantly improved, ensuring high electrical conductivity and thermal conductivity of the parts, while avoiding oxidation and porosity problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119525515A_ABST
    Figure CN119525515A_ABST
Patent Text Reader

Abstract

A method for improving the density of a copper alloy part comprises the following steps that forming is conducted, specifically, dry copper alloy powder is selected and laid layer by layer through a binder spraying 3D printing technology, and a binder is selectively sprayed through a slice pattern of the part till a 3D printing model is completed; curing is conducted, specifically, the printed 3D printing model is subjected to thermocuring, and after thermocuring, powder cleaning is conducted to obtain a copper alloy green body; degreasing: degreasing the copper alloy green body in a vacuum degreasing furnace to obtain a degreased green body; and sintering is conducted, specifically, the degreased blank is subjected to sectional type sintering and then cooled to the room temperature along with a furnace, and the copper alloy part is obtained. After the copper alloy powder is subjected to jet printing forming through a binding agent, under the vacuum thermocuring process, a printed model has certain strength, and oxidation cannot be generated; the binder is effectively removed through vacuum degreasing, the quality and performance of the subsequent sintering process are guaranteed, and the compactness of the part is remarkably improved through segmented sintering and furnace cooling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the density of a copper alloy, and in particular to a method for improving the density of a copper alloy by binder jetting 3D printing. Background Art

[0002] Copper and its alloys have high thermal conductivity, electrical conductivity and machinability, and are widely used in aerospace, automobile, power and other fields. Due to its high thermal conductivity, it is one of the main raw materials for heat exchangers and radiators. However, traditional manufacturing processes face many challenges in processing complex geometric structures and high-performance components, making the manufacturing cost of complex components high and the cycle long.

[0003] 3D printing technology, also known as additive manufacturing technology, is an advanced manufacturing method that can overcome these challenges to a certain extent by forming three-dimensional parts by stacking materials layer by layer. Major technologies such as selective laser melting (SLM) and electron beam melting (EBM) provide a variety of possibilities for 3D printing of copper and copper alloys. These technologies can not only achieve high-precision and complex geometric structure manufacturing, but also significantly improve material utilization and reduce manufacturing costs.

[0004] However, copper's high reflectivity and high thermal conductivity make it face unique challenges in the 3D printing process. For example, in SLM technology, copper has a low absorption efficiency of laser energy, resulting in insufficient melting, and high thermal conductivity easily leads to rapid heat diffusion, affecting the stability of the molten pool and the molding quality, causing the deposited layer to curl, delaminate, and produce pores, resulting in part performance defects. Binder jetting technology constructs parts at room temperature, does not require high energy input, can effectively avoid defects and is lower cost. However, binder jet 3D printing copper and copper alloys are difficult to sinter and densify, which affects the mechanical properties and thermal conductivity of the parts. Summary of the invention

[0005] Based on this, the present invention proposes a method for improving the density of copper alloys in binder jet 3D printing. The problem of low sintering density and poor mechanical properties of copper alloys in binder jet technology is overcome. The method has excellent mechanical properties while ensuring high density.

[0006] A method for improving the density of copper alloy parts comprises the following steps:

[0007] Molding: Use dry copper alloy powder to apply powder layer by layer through the binder jet 3D printing process and selectively spray the binder through the slice pattern of the part until the 3D printed model is completed;

[0008] Curing: The 3D printed model is thermally cured, and the powder is removed after thermal curing to obtain a copper alloy green body;

[0009] Degreasing: placing the copper alloy green body in a vacuum degreasing furnace for degreasing to obtain a degreased green body;

[0010] Sintering: The degreased green body is sintered in sections, and then cooled to room temperature in the furnace to obtain copper alloy parts.

[0011] After the copper alloy powder is formed by binder jet printing, the printed model not only has a certain strength but also does not produce oxidation under the vacuum heat curing process; the binder is effectively removed by vacuum degreasing to ensure the quality and performance of the subsequent sintering process, and the density of the parts is significantly improved through segmented sintering and furnace cooling.

[0012] In one embodiment, the staged sintering in the sintering step is divided into two steps, the first step adopts vacuum sintering, and the second step adopts partial pressure sintering, wherein the temperature of partial pressure sintering is higher than the temperature of vacuum sintering.

[0013] This method of vacuum sintering combined with partial pressure sintering can clean the sintering environment while finely controlling the sintering atmosphere, thereby achieving better sintering results. Through the first step of low-temperature sintering, the green body can achieve initial densification at low temperatures to avoid premature grain growth; the second step of sintering at a higher temperature can further promote the closure of pores without significantly affecting the grain size, thereby improving the mechanical properties of the green body.

[0014] In one embodiment, the vacuum sintering temperature in the debinding step is lower than the vacuum sintering temperature in the sintering process.

[0015] The vacuum sintering temperature in the debinding step is lower than the vacuum sintering temperature in the sintering process. Through this stepped temperature setting, the printed body can be completely debound, and the sudden increase in temperature can be avoided to cause a sudden change in the grain size in the body, which affects the performance of the final copper alloy parts.

[0016] In one embodiment, the first step is vacuum sintering, heating to a preset temperature at 5-15°C / min, and keeping the temperature for 1-3 hours; the preset temperature is Ts-(50-200°C);

[0017] Where Ts is the solidus temperature of the copper alloy.

[0018] The first step is vacuum sintering. At the initial stage of parts sintering, the heating rate is relatively fast, which improves the sintering efficiency.

[0019] In one embodiment, the second step is partial pressure sintering, the temperature is raised to a preset temperature at 1-5°C / min, and the temperature is kept for 2-5 hours; nitrogen is introduced during the sintering process, the nitrogen introduction rate is 2-10L / min, and the furnace is cooled;

[0020] The calculation formula of the preset temperature is: Ts+k(Tl-Ts),

[0021] Wherein, Ts is the solidus temperature of the copper alloy, k is 0.2-0.5, and Tl is the liquidus temperature of the copper alloy.

[0022] During the second step of partial pressure sintering, the heating rate is relatively low, mainly to avoid excessively fast heating rate causing large thermal stress inside the parts.

[0023] In one embodiment, during the partial pressure sintering step, nitrogen is introduced while vacuuming is continuously performed.

[0024] During partial pressure sintering, since nitrogen is introduced, in order to ensure that the sintering environment and atmosphere meet the requirements, it is necessary to vacuum the sintering in a timely manner.

[0025] In one embodiment, the thermal curing in the curing step is performed in a vacuum curing furnace with a curing temperature of 100-180°C, a holding time of 60-240 min, a heating rate of 1-10°C / min; a vacuum pressure value of 0.1-1 KPa, and a vacuum pressure rate of 1-10 KPa / min.

[0026] The binder inside large-sized parts is affected by heat transfer and heats up relatively slowly. If the temperature rises too quickly, the external binder may have solidified while the internal binder is still in liquid form, which will cause problems such as internal stress concentration. In addition, to prevent the curing and cross-linking reaction from being too intense, the heating rate should not be too fast. This application sets the heating rate at 1 to 10°C / min based on the part size, which can meet both the curing efficiency and the curing quality.

[0027] In one embodiment, the degreasing process is as follows:

[0028] The degreasing and curing furnace is evacuated to 1-20 Pa;

[0029] Inert gas is introduced, and the gas flow rate of the inert gas is controlled at 2-10 L / min;

[0030] Raise the temperature to 400-700℃ and keep it warm for 4-8h;

[0031] The inert gas is hydrogen and / or argon.

[0032] The use of inert gas in the degreasing step can prevent the copper alloy blank from being oxidized; and the introduction of hydrogen for degreasing can also effectively remove the residues produced by the decomposition of the binder, while also reducing metal oxides, reducing oxygen content, and improving the quality and conductivity of sintered parts.

[0033] In one embodiment, in the forming step, the copper alloy powder is a CuCr-based powder with a particle size distribution of 0 to 30 μm; and the 3D printing model adopts a hollow structure design.

[0034] The hollow structure design can, on the one hand, effectively remove the binder and prevent the binder residue from affecting the performance of the copper alloy sintered parts; on the other hand, it can effectively reduce the waste of binder.

[0035] In one embodiment, the binder used for binder jet printing is a low carbon residue water-based binder.

[0036] The use of low-residue carbon water-based binder for 3D printing can not only improve the conductivity of copper alloy parts after sintering, but also help improve properties such as strength.

[0037] The copper alloy blank formed by binder jet 3D printing undergoes vacuum degreasing, which not only effectively removes the binder, but also prevents the blank from oxidation. It then undergoes a staged sintering and furnace cooling process to improve the density and mechanical properties of the copper alloy parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The pores and metallographic images of the copper alloy parts in Example 1

[0039] Figure 2 Copper alloy parts pores and metallographic diagram for example DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of the present invention, a plurality of embodiments will be given below to describe the present invention more comprehensively. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood. The binder jet 3D printing (3DP or BJ) herein is based on the working principle that the powder spreader lays a layer of powder, and then the print head sprays the binder at the position where the molding is required according to the slice pattern of the three-dimensional model, and prints layer by layer to finally form a three-dimensional printed green body. The hollow structure design herein refers to reducing the amount of binder sprayed or the number of sprays in the part where the strength requirement of the part is not high or the inner core position during the binder jet printing process. The appearance, shape, size, etc. of the printed model are not changed. The model and blank herein are generally referred to as a three-dimensional model formed by binder jet printing or a blank after curing or degreasing. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0041] In one embodiment, a method for improving the density of a copper alloy part comprises the following steps:

[0042] Molding: Use dry copper alloy powder to apply powder layer by layer through the binder jet 3D printing process and selectively spray the binder through the slice pattern of the part until the 3D printed model is completed;

[0043] Curing: The 3D printed model is thermally cured, and the powder is removed after thermal curing to obtain a copper alloy green body;

[0044] Degreasing: placing the copper alloy green body in a vacuum degreasing furnace for degreasing to obtain a degreased green body;

[0045] Sintering: The degreased green body is sintered in sections, and then cooled to room temperature in the furnace to obtain copper alloy parts.

[0046] The copper alloy blank formed by binder jet 3D printing is vacuum sintered, which can not only effectively remove the binder, but also vacuum degrease to prevent the blank from oxidation. The density and mechanical properties of the copper alloy parts are improved through segmented sintering and furnace cooling processes.

[0047] The method for improving the density of copper alloy parts is described below in conjunction with specific embodiments. In order to further illustrate the advancement and practical effectiveness of the technical solution of the present application, specific embodiments are now given to further understand the concept of the method for improving the density of copper alloy parts.

[0048] Embodiment 1

[0049] Molding: Water-atomized CuCr alloy powder is used for printing through a binder jet 3D printing process. The Cr content is 0.95wt.%, and the powder particle size distribution is within 0-10 microns. Before printing, the powder is placed in a vacuum oven at 100°C for 2 hours to make it completely dry. During printing, the prepared and dried CuCr alloy powder is placed in a powder spreading device for layer-by-layer powder spreading. The printing device selectively sprays a binder on the CuCr alloy powder layer according to the slicing pattern of the copper alloy part. Until the printed model is completed. The printed model adopts a hollow structure design, and the binder adopts a low-residual carbon water-based binder.

[0050] Description: Water atomized powder is a metal or alloy powder prepared by water atomization. Water atomization is a process in which liquid metal or alloy is impacted by high-pressure water flow to break it into tiny droplets, and then the droplets are rapidly cooled and solidified in water to form powder particles.

[0051] After drying, the CuCr alloy powder can avoid moisture absorption and agglomeration, which affects the printing quality. The use of low-residual carbon water-based binder can reduce the residual carbon content of subsequent green body sintering and improve the comprehensive mechanical properties of alloy parts.

[0052] Curing: Place the completed 3D printed model in a vacuum curing furnace for thermal curing. During curing, evacuate the curing furnace at a rate of 5KPa / min, so that the vacuum pressure value in the furnace is 0.5KPa, and then heat up to 150℃ at a rate of 10℃ / min and keep warm for 120min. After cooling with the furnace, remove the excess loose powder to obtain the copper alloy solidified green body. According to the test, the density of the copper alloy green body can reach 57.6% after this step.

[0053] Degreasing: Place the solidified copper alloy green body on an alumina ceramic plate and put it into a sintering furnace. Evacuate to 2Pa, introduce a mixed gas of H2+Ar at a gas flow rate of 3L / min, and heat to 600℃ at a rate of 5℃ / min and keep warm for 4h for sufficient degreasing.

[0054] Hydrogen degreasing can effectively remove the residues produced by the decomposition of organic binders, and at the same time can reduce metal oxides and reduce oxygen content to avoid affecting the sintering quality and final conductivity of sintered parts.

[0055] Sintering: The degreased body is sintered in two stages. In the first stage, the temperature is raised to 950°C at 5°C / min in a vacuum environment for vacuum sintering and kept at this temperature for 2 hours. Then, before the second stage of partial pressure sintering, the sintering furnace chamber is evacuated to remove the impurity gas and moisture in the furnace. Then the temperature is raised to 1080°C at 2°C / min and kept at this temperature for 3 hours. Nitrogen is introduced during the sintering process at a flow rate of 4L / min, and then cooled to room temperature with the furnace to obtain a copper alloy sintered test block.

[0056] In the first step of vacuum sintering, the heating rate is slightly higher, which improves the sintering efficiency while ensuring the sintering quality; in the second step of partial pressure sintering, the heating rate is lower than the first step, mainly to avoid the heating rate being too fast, which may cause large thermal stress inside the parts and affect the accuracy and performance of the parts.

[0057] After testing, the density of copper alloy after segmented sintering can reach more than 98%, and its pores and metallographic structure are as follows Figure 1 As shown. The tensile strength can reach more than 220MPa (before heat treatment). The heat treatment in brackets refers to the post-treatment process after sintering, such as the treatment means or process of further improving the performance of copper alloy through solid solution aging treatment.

[0058] Embodiment 2

[0059] Molding: Water-atomized CuCr alloy powder is used for printing through a binder jet 3D printing process. The Cr content is 0.5wt.%, and the powder particle size distribution is within 5 to 25 microns. Before printing, the powder is placed in a vacuum oven at 100°C for 2 hours to make it completely dry. During printing, the prepared and dried CuCr alloy powder is placed in a powder spreading device for layer-by-layer powder spreading. The printing device selectively sprays a binder on the CuCr alloy powder layer according to the slicing pattern of the copper alloy part. Until the printed model is completed. The printed model adopts a hollow structure design, and the binder adopts a low-residual carbon water-based binder.

[0060] After the CuCr alloy powder is dried, it can avoid the powder agglomeration due to moisture absorption, which affects the printing quality. The use of low residual carbon water-based binder can reduce the residual carbon residue during subsequent sintering of the green body, thus avoiding the high residual carbon content affecting the electrical conductivity and mechanical properties of the copper alloy.

[0061] Curing: Place the completed 3D printed model in a vacuum curing furnace for thermal curing. During curing, evacuate the curing furnace at a rate of 10KPa / min, so that the vacuum pressure value in the furnace reaches 0.1KPa, and then heat it to 160℃ at 5℃ / min and keep it warm for 150min. After cooling in the furnace, remove the excess loose powder to obtain the copper alloy solidified green body. According to the test, the density of the copper alloy green body can reach 58.3% after this step.

[0062] Degreasing: Place the solidified copper alloy green body on an alumina ceramic plate and put it into a sintering furnace. Evacuate to 8Pa, introduce H2 at a gas flow rate of 10L / min, and heat to 450℃ at a rate of 8℃ / min for 4h to fully degrease.

[0063] Hydrogen degreasing can effectively remove the residues produced by the decomposition of organic binders, and at the same time can reduce metal oxides and reduce oxygen content to avoid affecting the sintering quality and final conductivity of sintered parts.

[0064] Sintering: The degreased body was sintered in two stages. In the first stage, the temperature was raised to 1000°C at 10°C / min in a vacuum environment and kept at this temperature for 1.5 hours. In the second stage, the temperature was raised to 1085°C at 1°C / min and kept at this temperature for 3 hours by partial pressure sintering. Nitrogen was introduced during the sintering process at a flow rate of 8L / min, and then cooled to room temperature with the furnace to obtain a copper alloy sintered test block.

[0065] After testing, the density of copper alloy after segmented sintering can reach more than 98%, and its pores and metallographic structure are as follows Figure 2 As shown. The tensile strength can reach more than 180MPa (before heat treatment). The heat treatment in brackets refers to the post-treatment process after sintering, such as the treatment means or process of further improving the performance of copper alloy through solid solution aging treatment.

[0066] It should be noted that in the above two embodiments, in the second step of partial pressure sintering, in order to prevent the parts from being oxidized, the sintering furnace is always in a negative pressure environment, so it is necessary to properly evacuate the furnace according to the air pressure in the sintering furnace.

[0067] It can be seen from the above embodiments that, by adopting the technical solution of the present application, the copper alloy parts have very high strength after sintering (without subsequent treatment), and the density of the parts is significantly improved.

[0068] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0069] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for improving the density of copper alloy parts, characterized in that: The following steps are involved: Molding: Use dry copper alloy powder to apply powder layer by layer through the binder jet 3D printing process and selectively spray the binder through the slice pattern of the part until the 3D printed model is completed; Curing: The 3D printed model is cured by vacuum heat curing, and the powder is removed after heat curing to obtain the copper alloy green body; Degreasing: placing the copper alloy green body in a vacuum degreasing furnace for degreasing to obtain a degreased green body; Sintering: The degreased green body is sintered in sections, and then cooled to room temperature in the furnace to obtain copper alloy parts.

2. The method for improving the density of copper alloy parts according to claim 1, characterized in that: The segmented sintering in the sintering step is divided into two steps, the first step adopts vacuum sintering, and the second step adopts partial pressure sintering, wherein the temperature of the partial pressure sintering is higher than the temperature of the vacuum sintering.

3. The method for improving the density of copper alloy parts according to claim 2, characterized in that: The vacuum sintering temperature in the debinding step is lower than the vacuum sintering temperature in the sintering process.

4. The method for improving the density of copper alloy parts according to claim 2, characterized in that: The first step is vacuum sintering, heating to the preset temperature at 5-15°C / min and keeping the temperature for 1-3h; the preset temperature is Ts-(50-200°C); Wherein, Ts is the solidus temperature of the copper alloy.

5. The method for improving the density of copper alloy parts according to claim 2, characterized in that: The second step is partial pressure sintering, heating to the preset temperature at 1-5°C / min and keeping the temperature for 2-5h; nitrogen is introduced during the sintering process at a rate of 2-10L / min, and the furnace is cooled; The calculation formula of the preset temperature is: Ts+k(Tl-Ts), Wherein, Ts is the solidus temperature of the copper alloy, k is 0.2-0.5, and Tl is the liquidus temperature of the copper alloy.

6. The method for improving the density of copper alloy parts according to claim 5, characterized in that: During the partial pressure sintering step, nitrogen is introduced while vacuum is continuously drawn.

7. The method for improving the density of copper alloy parts according to claim 1, characterized in that: The curing temperature of vacuum thermal curing is 100-180°C, the holding time is 60-240min, and the heating rate is 1-10°C / min; the vacuum pressure value is 0.1-1KPa, and the vacuum pressure rate is 1-10KPa / min.

8. The method for improving the density of copper alloy parts according to claim 1, characterized in that: The degreasing process is as follows: The vacuum degreasing furnace is evacuated to 1-20Pa; Inert gas is introduced, and the flow rate of the inert gas is 2 to 10 L / min; Raise the temperature to 400-700℃ and keep it warm for 4-8h; The inert gas is hydrogen and / or argon.

9. The method for improving the density of copper alloy parts according to claim 1, characterized in that: In the forming step, the copper alloy powder is a CuCr-based powder with a particle size distribution of 0 to 30 μm.

10. The method for improving the density of copper alloy parts according to claim 1, characterized in that: The binder used for binder jet printing is a low carbon residual water-based binder.

Citation Information

Cited By

  • Method and device for preparing porous ZnO / Zn bone reconstruction scaffold through adhesive jet 3D printing

    CN119870498A

  • Medical degradable metal zinc alloy, manufacturing method and application

    CN120362512A

  • Short-period, low-cost and high-performance copper alloy and preparation method thereof

    CN120940657A